A Juridical Analysis of Court Decision Number 92/Pdt.Sus-HKI/Copyright/2024/Commercial Court at the Central Jakarta District Court (Copyright Infringement Case Involving Agnes Monica) - I Gusti Ngurah Deva Aditya Laksmana Putra; Maidah Purwanti; Masdar Bakhtiar (DE'RECHTSSTAAT, 2026)
This study aims to analyze the determination of legal subjects and the legal consequences of Court Decision Number 92/Pdt.Sus-HKI/Copyright/2024/PN Niaga Jkt.Pst regarding the copyright infringement of the song "Bilang Saja" by Agnes Monica Muljoto. According to prevailing legal norms, the concert organizer, in this case PT Aneka Bintang Gading, should have been held responsible for the commercial use of the copyrighted work, rather than the singer who merely performed. However, the court decision designated Agnes Monica as the main defendant, which is inconsistent with the principles of justice, legal certainty, and utility as formulated by Gustav Radbruch. The legal consequences of this decision create uncertainty within the entertainment industry and have the potential to hinder the growth of Indonesia's creative economy. This research applies a normative approach with qualitative analysis of relevant legislation and legal documents. The findings highlight the necessity of accurately determining the responsible legal subject in copyright disputes to ensure fair and proportional legal protection for all parties involved.